A boundary element and radial basis function method for the Cattaneo–Vernotte equation in anisotropic media with spatially varying and temperature dependent properties - Ang, Whye Teong (2023)
A numerical method based on boundary integral equation formulation and radial basis function approximation is presented for the numerical solution of the Cattaneo–Vernotte hyperbolic equation in anisotropic media with spatially varying and temperature dependent properties. Specific test problems are solved to verify the validity and accuracy of the proposed numerical procedure.